Increased expression of GAB1 promotes inflammation and fibrosis in systemic sclerosis. Issue 11 (18th December 2019) - Shi, Xiangguang; Liu, Qingmei; Zhao, Han; Lu, Jiaying; Huang, Yan; Ma, Yanyun; Xia, Jingjing; Liu, Mengguo; Tu, Wenzhen; Jin, Li; Wang, Jiucun; Zhao, Yinhuan; et al.
Abstract: Systemic sclerosis (SSc) is an autoimmune disease mainly characterized by persistent inflammation and fibrosis. The receptor tyrosine kinase (RTK) signal pathway plays an important role in the process of SSc, and Grb2‐associated binding protein (GAB) is crucial in activating RTK signalling. A previous study found elevated levels of GAB1 in bleomycin (BLM)‐induced fibrotic lungs, but the effects of GAB1 in SSc remain unclear. Our aim was to investigate whether GAB1 was dysregulated and its potential role in SSc. Compared with healthy donors, we found GAB1 expression was 1.6‐fold higher in peripheral blood mononuclear cells (PBMC), 2.5‐fold higher in CD4 + T cells, and 2‐fold higher in skin from of SSc patients ( P  < .01). At the same time, the levels of type one collagen (COLI) were also significantly increased (1.8‐fold higher) in SSc skin. Additionally, BLM‐induced SSc mice showed mRNA levels of Gab1 2‐fold higher than saline‐treated controls, and Gab1 expression correlated positively with collagen content. A further in vitro study showed silencing of GAB1 suppressed inflammatory gene expression in TNF‐α induced fibroblasts. Additionally, GAB1 deficiency prominently inhibited cell proliferation and reduced COLI protein levels in TGF‐β induced fibroblasts. Taken together, these data suggest that GAB1 has a relatively high expression rate in SSc, and knockdown of GAB1 may attenuate SSc by stimulating inflammatory and fibrotic processes.